HUBUNGAN STATUS GIZI IBU SELAMA HAMIL DENGAN KEJADIAN STUNTING PADA BAYI USIA 0-12 BULAN DI WILAYAH KERJA PUSKESMAS KENJERAN SURABAYA - Diyah Arini; Dwi Ernawati; Aida Berlian (Jurnal EDUNursing, 2020)
ABSTRACTMaternal nutritional status during pregnancy explains that maternal weight gain during pregnancy is recommended based on body mass index before pregnancy. Mothers who experience poor nutritional status are at risk of giving birth to LBW infants so that children are at risk of stunting. The purpose of the study was to analyze the relationship of maternal nutritional status during pregnancy with the incidence of stunting in infants aged 0-12 months in the work area of Kenjeran Health Center Surabaya. The design of the analytical correlation study with the retrospective cohort approach in 4 sub-districts included Kenjeran, Bulak, Kedung Cowek, Sukolilo Village. The sample technique used Stratified Random Sampling as many as 108 mothers who had infants aged 0-12 months. Data retrieval is done by questionnaire sheets and observations using KIA books, midline and z-score tables. The results of the study showed that most mothers experienced nutritional status during pregnancy. Mothers who experience nutritional status during pregnancy are less likely to cause children at risk of stunting. The Spearman rho test showed a correlation between maternal nutritional status during pregnancy and the incidence of stunting ρ = 0,000 (ρ <α = 0.05). The implication of this study is that the nutritional status of mothers during pregnancy is related to the incidence of stunting, so that it can be socialized about health education about stunting and nutritional needs that must be met during pregnancy to health workers at the Kenjeran Health Center Surabaya. Keywords: Maternal Nutritional Status During Pregnancy, Stunting, Infants